The long journey through renal filtration: new pieces in the puzzle of slit diaphragm architecture. Issue 3 (May 2017) - Conti, Sara; Perico, Luca; Grahammer, Florian; Huber, Tobias B.
Abstract : Purpose of review: The podocyte slit diaphragm is probably the least understood component of the kidney filtration barrier. In this review, we aim to integrate the most recent findings on the molecular make-up and structural architecture of this specialized cell–cell junction into a current concept of glomerular filtration. Recent findings: Analysis of cryopreserved mammalian tissue revealed a bipartite composition of the slit diaphragm. Single NEPH1 molecules span the lower part of the slit close to the glomerular basement membrane whereas NEPHRIN molecules are positioned in the apical part toward Bowman's space. This molecular arrangement could lead to heterogeneous ellipsoidal and circular pores, which are mainly located in the central region of the slit diaphragm. Summary: Despite having been first identified in the 1970s, the slit diaphragm's structural architecture has not been fully elucidated to date and remains an area of intense research and scientific debate. The slit diaphragm has been initially described as a rigid 'zipper-like' structure in which periodic, rod-like units extend from a podocyte foot processes to a linear central bar, giving rise to homogeneous 4 × 14 nm pores. Several recent findings have challenged these long-held beliefs and instead pointed to an unanticipated complexity of slit diaphragm structure. High-resolution ultrastructural analysis found evidence that the slit diaphragm is a dynamic and adjustable cell-cell junction that forms a nonclogging barrier within the renal filtration system.